Is Routine Contralateral Exploration Necessary while Doing Herniotomy for Unilateral Inguinal Hernia in Children? (TAJ: Journal of Teachers Association, 2011)
Routine contralateral exploration in infants and children with unilateral inguinal hernia has been practiced by a number of paediatric surgeons based on a presumed high incidence of patent processus vaginalis. Our aim is to report the incidence of contralateral manifestations after repair of unilateral inguinal hernia. A total of 217 patients were regularly followed-up at the department of paediatric surgery in Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) from February 1995 to June 2001 in order to determine if contralateral hernia developed after unilateral herniotomy. The overall incidence of contralateral manifestations was 6.45%. The average incidence for contralateral hernia in infants upto 1 year was 11.68%. However, the incidence fell significantly in older children. With such low incidence of contralateral hernia after unilateral herniotomy, the authors do not feel to recommend contralateral exploration for unilateral inguinal hernia.   DOI: http://dx.doi.org/10.3329/taj.v14i2.8385 TAJ 2001; 14(2): 53-55